The splicing regulators Tra and Tra2 are unusually potent activators of pre-mRNA splicing. - Sciabica, K.S.; Hertel, K.J. (Nucleic Acids Research, 2006)
Sexual differentiation in Drosophila is regulated through alternative splicing of doublesex. Female-specific splicing is activated through the activity of splicing enhancer complexes assembled on multiple repeat elements. Each of these repeats serves as a binding platform for the cooperative assembly of a heterotrimeric complex consisting of the SR proteins Tra, Tra2 and 9G8. Using quantitative kinetic analyses, we demonstrate that each component of the enhancer complex is capable of recruiting the spliceosome. Surprisingly, Tra, Tra2 and 9G8 are much stronger splicing activators than other SR protein family members and their activation potential is significantly higher than expected from their serine/arginine content. 9G8 activates splicing not only through its RS domains but also through its RNA-binding domain. The RS domains of Tra and Tra2 are required but not sufficient for efficient complex assembly. Thus, the regulated assembly of the dsx enhancer complexes leads to the generation of an extended activation domain to guarantee the 'all or none' splicing switch that is required during Drosophila sexual differentiation.